Biomagnification and fate of persistent organic pollutants (POPs) in marine mammal food webs in the Northeastern Pacific Ocean - Cullon, Donna Lynn (2010)
Elevated polychlorinated biphenyl (PCB) concentrations have been detected in marine mammals inhabiting the Strait of Georgia, British Columbia (Canada) and Puget Sound, Washington State (USA). This raises concerns about adverse health effects and underscores the importance of documenting source, transport, and fate of contaminants. This marine mammal-oriented study- (1) examines dietary exposure to complex mixtures of persistent organic pollutants (POPs); (2) characterizes POP accumulations using congener-specific contaminant analyses, stable isotope ratios, and multivariate statistical methods; and (3) explores some of the influencing factors for POP bioaccumulation in marine mammals. A first application of a food basket approach to assessing real-world dietary exposure to mixtures of chemicals in marine mammals has revealed Puget Sound as a regional “hotspot” for PCB contamination. The consistency between PCB concentrations in Puget Sound and the Strait of Georgia harbour seals (Phoca vitulina) and their food baskets validates the use of this method as a basis for exploring dietary exposure, metabolism, biomagnification, and health risks in marine mammals. Concentration rankings of POPs and estimated daily intakes based on our food baskets suggests that both legacy (e.g., PCB, dichlorodiphenyltrichloroethane [DDT]) and new (polybrominated diphenyl ethers [PBDEs]) POPs may pose potential health risks to seals. Accumulations of PCBs in the Strait of Georgia seal food web demonstrate the bioaccumulative nature and persistence of PCBs. Correlations of PCB concentrations with physicochemical properties and trophic level revealed the important role that metabolism plays in biomagnification in seals, alongside trophic level and log Kow. We estimate a PCB load of 77 kg within the Strait of Georgia biomass, with the largest proportion (36 %) detected in marine mammals. Dietary exposure of POPs to resident killer whales (Orcinus orca) was assessed by measuring POPs in four stocks of chinook salmon (Oncorhynchus ...